Identification of Meloidogyne spp. (Tylenchida: Meloidogynidae) as potato tuber-borne nematodes (PTBN) in the potato production center of Java Island, Indonesia - Wawan Kurniawan; Supramana Supramana; Giyanto Giyanto; Abdul Munif (Universitas Lampung, 2026)
Root-knot nematodes (Meloidogyne spp.) are among the most destructive plant-parasitic nematodes affecting potato production worldwide. However, information on Meloidogyne spp. associated with potato tubers and their potential as potato tuber-borne nematodes (PTBN) in Indonesia remains limited. This study aimed to identify Meloidogyne species associated with potato tubers and determine their distribution in major potato-producing regions of Java, Indonesia. Surveys were conducted from January 2023 to December 2024 in West, Central, and East Java. Symptomatic potato tubers were collected and examined using morphological, morphometric, and molecular approaches. Tubers were stored under refrigerated conditions for 3–24 months to evaluate nematode persistence. Molecular identification was performed using species-specific SCAR markers, followed by phylogenetic and sequence homology analyses. Root-knot nematodes were detected in all surveyed production areas and were associated with characteristic symptoms, including knobby, branched, elongated, and russeted tubers. Two species were identified: Meloidogyne incognita, which was widely distributed throughout Java, and Meloidogyne javanica, which was detected only in Cikandang Village, Garut, West Java. The nucleotide sequences were deposited in GenBank under accession numbers LC894939–LC894951 (M. incognita) and LC894966 (M. javanica). Both species remained viable in potato tubers for up to 24 months, confirming their potential as PTBN. These findings provide a scientific basis for strengthening nematode-free seed certification and phytosanitary measures to reduce the spread of Meloidogyne spp. through seed tubers.